EQ-5D-3L full health state discriminates between drug and placebo in clinical trials of systemic lupus erythematosus. (27th January 2021) - Lindblom, Julius; Gomez, Alvaro; Borg, Alexander; Emamikia, Sharzad; Ladakis, Dimitris; Matilla, Joaquin; Pehr, Martin; Cobar, Flordelyn; Enman, Yvonne; Heintz, Emelie; Regardt, Malin; Parodis, Ioannis
Abstract: Objectives: The objectives of this study were to investigate the discriminative ability of EQ-5D-3L full health state (FHS) in clinical trials of SLE, and to identify factors associated with FHS after treatment. Methods: Data from the BLISS-52 (NCT00424476) and BLISS-76 (NCT00410384) trials of belimumab ( N  = 1684) were utilized. FHS was defined as a response of no problems in all five EQ-5D-3L dimensions, yielding an index score of 1. The Pearson's χ 2 or Fisher's exact test was employed for comparisons, and logistic regression for adjustments and assessment of independence. Results: We demonstrated higher EQ-5D-3L FHS frequencies among patients given standard therapy (ST) plus the licensed belimumab dose vs ST alone (26.1% vs 19.4%; P = 0.001; week 52), and within SRI-4 responders vs non-responders (27.0% vs 19.8%; P < 0.001; week 52) from weeks 36 to 52. In multivariable regression analysis, SLEDAI-2K (OR: 0.90; 95% CI: 0.87,  0.94; P < 0.001) and SLICC/ACR Damage Index (OR: 0.79; 95% CI: 0.69, 0.91; P = 0.001) scores were independently associated with lower FHS frequencies at week 52, while adding monthly infusions of belimumab 10 mg/kg to ST favoured FHS perception (OR: 1.60; 95% CI: 1.15, 2.24; P = 0.006). Add-on belimumab 10 mg/kg yielded higher FHS frequencies in antimalarial users vs non-users (29.9% vs 20.1%; P = 0.011), and in anti-dsDNA- and anti-Sm- positive vs negative patients (31.4% vs 13.4%; P < 0.001 and 33.0% vs 22.6%; P = 0.010, respectively), whereas no significant differences were observed in patients given ST alone. Conclusion: EQ-5D-3L FHS distinguished belimumab from placebo and responders from non-responders, and exhibited known-group validity in subgroup analysis. FHS may prove a useful patient-reported outcome in SLE studies.